2020
DOI: 10.1016/j.ijrefrig.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of the use of R1234yf and R1234ze(E) as drop-in alternatives of R134a in a water-to-water heat pump

Abstract: In the present paper, the experimental results of the use of R1234yf and R1234ze(E) as dropin alternatives of R134a in a water-to-water heat pump are discussed. The heat pump is firstly tested with R134a, to establish the baseline performance, and, then, is tested with the two abovementioned refrigerants considering the same compressor shaft rotational frequency and the same outlet temperatures of the secondary fluids from the evaporator and the condenser. The obtained results show that, compared to the R134a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…R744 operates under high pressure, and is highly toxic and flammable [14][15][16]. Following the second generation, third-generation refrigerants were composed of chlorofluorocarbons (CFCs) [17][18][19] and hydrochlorofluorocarbon (HCFCs) [20][21][22], which are easy to use, can operate under low pressure, and are nontoxic. However, they have high GWP and ODP, contributing to ozone depletion and global warming.…”
Section: Introductionmentioning
confidence: 99%
“…R744 operates under high pressure, and is highly toxic and flammable [14][15][16]. Following the second generation, third-generation refrigerants were composed of chlorofluorocarbons (CFCs) [17][18][19] and hydrochlorofluorocarbon (HCFCs) [20][21][22], which are easy to use, can operate under low pressure, and are nontoxic. However, they have high GWP and ODP, contributing to ozone depletion and global warming.…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that, under the test conditions, the power consumption of HFO1234yf was 2.7% higher than that of HFC134a. Colombo et al 17 studied the running performance of HFO1234yf and R1234ze(E) in a water-to-water heat pump. Research showed that the heating capacity and the COP of HFO1234yf were decreased by 9.80% and 7.39%, compared to HFC134a, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…R744 operates under high pressure, and is highly toxic and flammable (Figure 5) [14][15][16]. Following the second generation, third-generation refrigerants were composed of chlorofluorocarbons (CFCs) [17][18][19] and hydrochlorofluorocarbon (HCFCs) [20][21][22], which are easy to use, can operate under low pressure, and are nontoxic. However, they have high GWP and ODP, contributing to ozone depletion and global warming.…”
Section: Introductionmentioning
confidence: 99%